Improving preseason soccer performance: a combination of super high-intensity continuous training and dribbling-based repeated-sprint training - Kusuma, I. D. M. A. W.; Kusnanik, N. W.; Prianto, D. A.; Bawono, M. N.; Pramono, B. A.; Fajar, M. K.; Pranoto, A.; Susanto, I. H.; Phanpheng, Y. Y. (Trends in Sport Sciences, 2026)
Introduction: The preseason phase is crucial for restoring fitness and preparing players for competitive demands. This study is the first to integrate super high-intensity continuous training (SHCT) with dribbling-based repeated sprint training (RST) as a sport-specific, high-intensity training method.